Perancangan Sistem Pompa dan Perpipaan pada Sistem Seawater Reverse Osmosis - Akh. Maulidi; Agus Dwi Santoso; Triyanti Irmiyana (Politeknik Negeri Madura, 2025)
The State Polytechnic of Madura (POLTERA), located in Sampang Regency, East Java, was established in 2012. Its location outside the city of Sampang and directly on the coast means that the groundwater source at POLTERA is brackish. Meanwhile, the municipal water supply (PDAM) has not yet reached the coastal area. Consequently, to meet its clean water needs, POLTERA has been purchasing three tanks of clean water each day. This water supply is not intended to meet consumable needs.This research will analyze the daily clean water needs at POLTERA and design the pump and pipeline for a sea water reverse osmosis (SWRO) system. The outcome of this research is a plan for the SWRO pump and piping lines based on a case study at the POLTERA campus. The research found that the daily clean water requirement at POLTERA is 170.33 m³.The pump and piping system in the SWRO works by flowing brackish water from a well into a pretreatment tank. The water is then filtered in stages through a 5-micron sediment filter, a 1-micron sediment filter, and a Granular Active Carbon (GAC) filter to remove particles and harmful substances. It is then pumped at a pressure of 1015 bar to meet the requirements of the RO process. Next, the water enters the RO membrane to produce fresh water, which is stored in a storage tank. The water then passes through a post-carbon filter to improve its smell and taste before finally being ready for consumption.